Pelaksanaan Praktek lapangan Industri (PLI) Pada Mahasiswa Jurusan Kesejahteraan Keluarga Fakultas Teknik Universitas Negeri Padang - almi, nora; adriani, adriani; idrus, yenni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
Abstract This study aims to describe the implementation process Field Industrial (PLI)Faculty of Engineering, Department of Family Welfare Padang State University. This type ofresearch